Релейная защита электроэнергетических систем: учебное пособие - Андреев М. В. Михаил Владимирович; Рубан Н. Ю. Николай Юрьевич; Суворов А. А. Алексей Александрович; Гусев А. С. Александр Сергеевич; Сулайманов А. О. Алмаз Омурзакович (Томск, Изд-во ТПУ, 2018)
Заглавие с титульного экрана